Sudan : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the economic conditions in Sudan have been challenging since the secession of South Sudan in 2011 and the loss of the bulk of oil production and exports. The authorities have implemented partial policy adjustments to help stabilize the economy and reestablish growth, most recently by allowing for greater exchange rate flexibility and reducing fuel subsidies. The current account deficit (cash basis) is expected to decline by 3.25 percentage points to 2.75 percent of GDP in 2017. Data for the first half of 2017 indicate weaker real domestic demand, partly offset by a strengthening contribution from net exports.